An inferred dialogue between Dietrich Bonhoeffer and Carl Schmitt with a reconsideration of Stellvertretung from the jurisprudential perspective - Lam, Jason (Stellenbosch Theological Journal, 2025)
Recent studies have revealed that Dietrich Bonhoeffer’s brother-in-law, Gerhard Leibholz, developed a close relationship with the Nazi jurist scholar Carl Schmitt. Moreover, traces of Schmitt’s influence can be detected in Bonhoeffer’s early writings. Concepts such as the “extraordinary” and Bonhoeffer’s response in such situations display a structural similarity to Schmitt’s ideas. This essay explores how this personal relationship and intellectual influence may have shaped Bonhoeffer’s thought, drawing an inferred dialogue between Bonhoeffer and Schmitt, particularly through Bonhoeffer’s Ethics. It also offers a reinterpretation of key theological ideas, including the crucial concept of Stellvertretung, as developed in Ethics. By doing so, this approach provides insights into Bonhoeffer’s decision to join the conspiracy and his composition of Ethics.